2022
DOI: 10.3389/fpls.2022.839457
|View full text |Cite
|
Sign up to set email alerts
|

CG and CHG Methylation Contribute to the Transcriptional Control of OsPRR37-Output Genes in Rice

Abstract: Plant circadian clock coordinates endogenous transcriptional rhythms with diurnal changes of environmental cues. OsPRR37, a negative component in the rice circadian clock, reportedly regulates transcriptome rhythms, and agronomically important traits. However, the underlying regulatory mechanisms of OsPRR37-output genes remain largely unknown. In this study, whole genome bisulfite sequencing and high-throughput RNA sequencing were applied to verify the role of DNA methylation in the transcriptional control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…This result indicates that CG methylation and CHG methylation are usually coupled to regulate gene expression, and CG and CHG methylation may show co-evolution during crop domestication. For example, the promoter of OsHXK1 is hypomethylated at CG and CHG sites, which leads to an increase in OsHXK1 expression, which in turn leads to a decrease in the starch content in rice [39]. While DNA methyltransferases maintain cytosine methylation in specific contexts, four DNA demethylases in A. thaliana (ROS1, DME, DML2, and DML3) can erase the methylation status of cytosines in all sequence contexts.…”
Section: Dna Methylation Reprogramming During Pear Domestication and ...mentioning
confidence: 99%
“…This result indicates that CG methylation and CHG methylation are usually coupled to regulate gene expression, and CG and CHG methylation may show co-evolution during crop domestication. For example, the promoter of OsHXK1 is hypomethylated at CG and CHG sites, which leads to an increase in OsHXK1 expression, which in turn leads to a decrease in the starch content in rice [39]. While DNA methyltransferases maintain cytosine methylation in specific contexts, four DNA demethylases in A. thaliana (ROS1, DME, DML2, and DML3) can erase the methylation status of cytosines in all sequence contexts.…”
Section: Dna Methylation Reprogramming During Pear Domestication and ...mentioning
confidence: 99%
“…We found that the number of articles in the past two or 3 years has increased significantly, as shown in the figure below (Figure 5). In vivo, circadian rhythms are regulated and maintained by endogenous clock genes (Oishi et al, 2005;Liu et al, 2022), which are involved in several physiological activities, including metabolism (Peek et al,FIGURE 4 Human studies of melatonin and osteoclast differentiation.…”
Section: Circadian Rhythm Genesmentioning
confidence: 99%
“…We found that the number of articles in the past two or 3 years has increased significantly, as shown in the figure below ( Figure 5 ). In vivo , circadian rhythms are regulated and maintained by endogenous clock genes ( Oishi et al, 2005 ; Liu et al, 2022 ), which are involved in several physiological activities, including metabolism ( Peek et al, 2017 ), cell cycle ( Han et al, 2016 ; Dong et al, 2019 ), sleep wake cycle ( Ikegami et al, 2019 ), bone formation ( Fu et al, 2005 ; Sato et al, 2007 ; Hirata et al, 2022 ; Zhao et al, 2022 ), and heart rate and blood pressure ( Wang et al, 2008 ). However, when clock gene expression is aberrant, the body experience abnormalities and possible disease, including sleep disorders ( Patke et al, 2017 ), diabetes ( Marcheva et al, 2010 ), obesity ( Paschos et al, 2012 ; Chaix et al, 2019 ), osteoporosis ( Tang et al, 2020 ), and tumors ( Altman et al, 2015 ).…”
Section: Circadian Rhythm Genesmentioning
confidence: 99%